Islamic Society and The Challenge of Globalization - Abdullah, Taufik (P2KK LIPI, 1998)
This early years Islamic Society face globalization era. Because of that they face several challenges; like social mobility. Globalization from the outside world has influence science and technology. From that situation, people in Islamic society must participation in world development and they must to have good planned social and economic strategies.